The Potential of Marine Bacteria in Plastic Biodegradation: A Review - Riswan, M; Ronal Kurniawan; Effendi, Irwan; Mega Novia Putri (Tropical Marine Environmental Sciences, 2025)
Ocean plastic pollution has become a significant problem affecting ecosystems and human health. One promising approach to address this issue is biodegradation by marine microorganisms, particularly bacteria. This article reviews recent studies (2021–2024) exploring the ability of marine bacteria to degrade plastics. Based on the research, certain marine bacteria have been proven capable of producing enzymes effective in breaking down various plastics. The article also discusses the challenges and opportunities in developing biotechnology based on marine bacteria to tackle plastic pollution